The effect of oil price to stock market in Europe countries (Bulgaria, Estonia, Hungary, Romania) / Nur Azwani Mohd Kamal - Mohd Kamal, Nur Azwani (2010)
This study tries to identify the relationship between oil prices and stock market in emerging markets of Europe Country. Data of weekly West Texas Intermediate Crude Oil (WTI) price and weekly price index of stock index from four emerging countries namely Bulgaria, Estonia, Hungary and Romania are selected as variables in this study. The data is collected for the five years period of 1 January 2005 to 31 December 2009 and used to estimate the Autoregressive Model. The results from this model reveal that there is significant and relationship between these two emerging markets where is Bulgaria and Estonia with the oil price movement. Furthermore, the analysis also shows Hungary and Romania has a relationship with oil price but there is no significant result due to the more significant on other macroeconomic variable. These results further our understanding of the interaction between oil prices and share prices and should be of use to investors, regulator, managers, and policy maker.